Food uniting neighbours (f.u.n.): a pilot study exploring the feasibility, acceptability, and preliminary impact of co-designed interventions to improve food access - Tamara Petresin; Marciane Any; Nayssam Shujauddin; Angela Annis; Jess Haines; f.u.n. Community Advisors (BMC Public Health)
Abstract Background Food insecurity remains a critical issue in Canada, with 15.6% of households affected. Food access, an important component of food security, reflects the ability of individuals to secure food. This pilot study aimed to assess the feasibility, acceptability, and preliminary impact of five co-designed interventions designed to improve nutritious food access in the Onward Willow neighbourhood of Guelph, ON. Methods Thirteen Community Advisors worked with University of Guelph researchers and used co-design to develop, implement, and pilot test five interventions to improve food access: community cafés, food skills workshops, grocery gift cards, gardening materials and workshops, and transportation support. The interventions were pilot tested with 159 community members, and feasibility and acceptability were assessed through surveys and interviews. Preliminary impact was assessed through quantitative pre-post or post-only Likert-scale survey measures. Results Findings show that the interventions were feasible and acceptable as all interventions were implemented per protocol and participant satisfaction was high across all interventions. Post-only evaluations identified that participants perceived that the community cafés helped to increase community connection and that the transportation support made it easier to have healthy foods available in their home. Pre-post evaluations revealed that the food skills workshops improved participants’ sense of community with a medium effect size (median = 4.12 [IQR 3.87–4.47] to 4.12 [IQR 3.91–4.87], p = .04, r = .33) and that the gardening materials and workshops resulted in increased fruit and vegetable availability with a large effect size (median = 3.00 [IQR 2.00–3.00] to 4.00 [IQR 3.00 to 4.00], p = .04, r = .78). Grocery gift cards did not result in any significant changes in food access outcomes. Conclusions Interventions that directly engage communities in creating solutions can be feasible, acceptable, and potentially effective. Future research is needed to explore long-term impacts of these interventions on diet quality and broader health outcomes.